Who is a teacher in Malawi? A study on graduate secondary school teachers with no education qualifications. - Saukila, Joyce (2018)
There is a teacher employment policy in secondary schools in Malawi in which the education system recruits graduates from any other disciplines that do not have the professional training of teachers. This policy has been there for decades and the number of such teachers has kept on increasing year after year. The sole purpose for this policy is to address the problem of shortage of teachers in secondary schools. These teachers are called ‘professionally unqualified’. Hence, the research is looking at how the professionally unqualified teachers (PUTs) solve the challenges they meet in teaching? How these teachers have learnt about the teaching job?, the roles that schools play in the life of these PUTs and the role that the Directorate of Inspection and Advisory services (Where I work) can play to improve on the implementation of this policy. The study adopted a qualitative design of research. The study was purposefully and conveniently carried out in public secondary schools among PUTs. Interviews were used to collect data from a sample of 6 PUT participants, of which 4 were males and 2 females. The study has revealed that these professional unqualified teachers meet different challenges as they work. Amongst the challenges there is a common challenge of lack of promotion due to lack of the professional training and certificate. The results also show that these teachers have found their own ways of solving this challenge by focusing on their learners’ progress and achievement. The PUTs have learnt about teaching job through In-Service Trainings (INSETs) which are held by the schools; school level supervision done by Heads of Departments (HODs); through their daily interaction with learners and asking some information and advice from the qualified teachers. These results suggests that the Ministry of Education Science and Technology (MOEST) can support these PUTs by empowering school management to carry out INSETs on methodologies and class management issues for these PUTs while they are waiting for the formal professional training. MOEST can also consider offering the UCE course online so that it can reach many 4 teachers at once and prevent turnover which is caused when teachers are withdrawn from schools for a year to do the course in a university campus.